SEJARAH ISLAM DAN TRADISI KEILMUAN DI ACEH - Imran Muhammad (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2020)
Almost all historians state that the area of Indonesia where Islam first entered is Aceh. Only among these experts, there are differences of opinion regarding the certainty of the coming year of Islam. To understand the dynamics of Islam in Aceh, among others, it can be traced through the history of the early entry of Islam to the archipelago, the role of ulama and umara (rulers), the function of educational institutions, and the way people understand and practice Islamic teachings. The values and behavior of life in Aceh shows the Islamic style in almost all its aspects. This is mainly due to the prevailing socialization institutions, namely dayah education which has produced militant clerics, who are not tired of leading the community towards deepening religious knowledge and the process of Islamization. Most of the rulers, including the Sultan, had received training from the ulama or at least received fatwas from them.